Strategic environmental assessment implementation of transport and mobility plans. The case of Italian regions and provinces - Andrea De Montis; Simone Caschili; Amedeo Ganciu; Antonio Ledda; Filippo Paoli; Federico Puddu; Mario Barra (Journal of Agricultural Engineering, 2016)
Transport and mobility plans imply strategies and actions that affect the environment. The European Union has introduced in 2001 the strategic environmental assessment (SEA) to take into account and mitigate adverse environmental effects in planning and decision-making. SEA limited implementation has attracted the interest of many scholars that have sought methods able to assess the quality of SEA processes by identifying vices and virtues in practice. In this paper, we measure the quality of eight SEAs for transport and mobility plans of regional and provincial administrations of Italy. Results show that the overall quality level of SEA reports is only barely sufficient, Abruzzo is among the virtuous and Piedmont among the critical administrations. We also stress that the determination of impact significance has received the worse quality score. We finally compare our results to other Italian and British homologous cases finding interesting and generally confirmative evidences.